Collaborative Governance in Indonesia’s Nutritious Food Policy: A Multi-Stakeholder Implementation Model - Nugroho, Alih Aji; Sudrajat, Agus; Azmi, Ilima Fitri; Ardiansyah, Fahri; Prasetyanti, Retnayu (Puslatbang KDOD Lembaga Administrasi Negara, 2025)
Indonesia continues to face substantial challenges in achieving food security andnutritional adequacy, with nearly 70% of its population unable to afford healthy diet and childhood stunting rates remaining above 20%. Addressing these complex, interlinked issues requires a coordinated, multisectoral response. This study critically examines the implementation of the National Nutritious Food Policy, focusing on the role of stakeholder collaboration within a proposed model that combines two collaborative perspectives, based on the cluster model and the Ansell & Gash collaborative frameworks. This has made the analysis relevant to both practical and theoretical contexts. By employing a qualitative analysis grounded in a literature review and policy analysis, the research identifies four strategic pillars essential to policy success: governance and policy management, food provision and distribution, inter-organizational collaboration and promotion, and monitoring and evaluation. The study emphasizes the need for an integrated institutional framework that aligns national priorities with local capacities, including the engagement of small and medium enterprises (SMEs), Village-Owned Enterprises (BUMDes), and community organizations. Findings highlight that sustained improvements in food security and public health outcomes depend on solid coordination, infrastructure development, and inclusive stakeholder participation. The study contributes to the growing discourse on collaborative governance in public policy, particularly in thecontext of national nutrition interventions. It offers practical insights for optimizing multi-actor implementation strategies in Indonesia’s food system.